Les secteurs floricoles d’Afrique de l’Est et la pandémie de Covid-19 - Olivier Ballesta (Belgeo)
East African floriculture is highly dependent on the European market, which has absorbed rapidly increasing volumes over the past twenty years. Kenya is the leading producer of cut flowers, ahead of Ethiopia, while the other countries in the region are much more marginal. The development of this export sector relies on a logistical organization that guarantees an appropriate access time for this perishable and fragile product by air. The Covid-19 pandemic and the mobility restrictions imposed in the main importing countries have suddenly disrupted the industry and deprived thousands of workers of their jobs. After the shock of the first wave in the spring of 2020, the sector has gradually recovered thanks to the conversion of several passenger planes and the more systematic use of specialized freight companies, whose role has never been so vital to the flower industry. Beyond its cyclical dimension, the pandemic highlights fundamental issues that the players will have to address to ensure the sustainability of this activity.